Japanese diaspora in Margaret Dilloway's How to be an American Housewife - Fitriani, Elok; Basuki, Imam; Setiawan, Ikwan; Supiastutik, Supiastutik (EduLite: Journal of English Education, Literature and Culture, 2024)
In today's borderless world, people move quickly, forming diaspora communities with complex cultural lives. The culture shock that causes mental health disruption is common in these diaspora communities. Therefore, the study of this diaspora is crucial to be conducted. The novel entitled How to be an American Housewife represents the difficulties of becoming a diaspora subject in a new country with a new culture. This study focuses on the diaspora experience undergone by Shoko Morgan. The study aims to show the construction of diaspora identity, the condition of the Japanese diaspora community in America, and the author's critical position. This descriptive qualitative research utilized the cultural identity and diaspora theory proposed by Stuart Hall to unveil the diaspora identity in the novel. This research reveals that identity is always in some process of adaptation, transformation, and differences from new environments. The literary work under scrutiny shows the experience of Japanese immigrants at that time, such as feeling alienated, isolated, and discriminated against. Through this novel, Margaret Dilloway has represented her mother's challenging life experiences as a diaspora subject in the USA.